Originally Posted by

**robeuler** the hard part is done for you. you have two equations, and one of them tells you one variable in terms of the other, without any additional manipulation.

you take y=-5x and plug that into the first equation. you have two choices with this:

(-5x)^2-9x^2=19

or, if you solve for x in the second equation (and get x=-(1/5)y)

y^2-9(-(1/5)y)^2=19

the first way is easier so lets stick to that.

(-5x)^2-9x^2=19

**25x^2**-9x^2=19

16x^2=19

x^2=19/16

x=sqrt(19/16).

now take this value for x and plug it into the second equation of our original pair.

y=-5sqrt(19/16)

hope this helps.